HEALTH OF MEDICAL WORKERS AND RISK FACTORS AFFECTING THEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Currently, it has been proven that one of the main reasons for the high morbidity of medical workers is the specificity of professional activity. Today, in domestic and foreign research, the interest in interaction with professional activity, people's behavior and health has increased significantly. Health care behavior of medical personnel is observed as the ability of the body to maintain and activate compensatory, protective, regulatory mechanisms that ensure work efficiency in all conditions of professional activity. Therefore, the issues of strengthening the health of doctors in modern healthcare institutions are fully raised.